DEVELOPING YOUTH HUMAN CAPITAL CAPABILITIES TO INCREASE THE NATIONAL ENTREPRENEURSHIP RATIO - Muhammad Adsan; Marthalina; Muhadam Labolo (KOMITMEN: Jurnal Ilmiah Manajemen, 2026)
The Youth Entrepreneurship Ratio in Indonesia's 2025-2029 National Medium-Term Development Plan remains unmet, with 2025 realization reaching only 1.17 percent against a 1.33 percent target. This study analyzes the problem from a public-sector human resource management perspective, treating the programs of the Ministry of Youth and Sports (Kemenpora) as human capital investments whose effectiveness is determined by capability conversion. The theoretical framework combines human capital theory and the capability approach. Using a qualitative case-study design with seventeen purposively selected key informants, complemented by documentation review and triangulation, the data were analyzed thematically according to capability dimensions and conversion factors. The findings show that Kemenpora's programs have formed an investment portfolio covering cognitive, psychological, social, and enabling capability dimensions, yet with uneven emphasis. The conversion effectiveness from program outputs to ratio outcomes is low, mainly due to weak post-training mentoring and limited access to capital and digital infrastructure, while regional disparities reflect differences in conversion factors. The study recommends shifting the orientation from outputs toward capabilities and outcomes, balancing the development of all four dimensions, strengthening region-differentiated enabling factors, and adopting evaluation based on surviving ventures.